Needs assessment: strategy of integration disaster education at elementary schools in disaster prone areas - Septikasari, Zela; Retnawati, Heri; Wilujeng, Insih; Shaw, Rajib; Handaka, Irvan Budhi (Intelektual Pustaka Media Utama, 2024)
This research was conducted to analyze integration disaster education strategies in elementary schools located in disaster-prone areas. This research is qualitative research using descriptive design. This research used interview instrument in data collection. The respondents were 23 elementary school teachers in Sleman Regency, Special Region of Yogyakarta. The results found that the integration of disaster education is carried out through subjects, study tours, discussions, and simulations. Strategies implemented in the integration of disaster education with interesting learning media, disaster training, improvement of school facilities and infrastructure, updating school disaster documents, and cooperation with disaster management institutions. The integration disaster education model expected by teachers is in the form of a website that contains separate materials for teachers and students. The website is expected to contain simple material packaged in the form of pictures, videos, sounds, animations, games, quizzes and songs. Maximizing integration disaster education strategies can be done by improving the internal and external quality of schools. School support, cooperation with disaster management stakeholders, the active role of teachers, and the support of school principals' policies in preparing for integration disaster education learning is expected so that disaster education can be implemented sustainably.